نظام الأجر وأثره على الإلتزام التنظيمي لموظفي السلك الخاص في مديرية التجارة - جيجل - عقون, شراف; بوخدوني, لقمان; عيساوي, عيساوي (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الدراسة إلى اختبار أبعاد نظام الأجر والمتمثلة في كل من نسب التعويضات والاقتطاعات وأثرها على الإلتزام التنظيمي لدى موظفي السلك الخاص في مديرية التجارة –جيجل، تم استخدام الإستبيان كأداة لجمع البيانات عن متغيرات الدراسة، وقد تم توزيعه على عينة مكونة من 60 موظفا بمديرية التجارة- جيجل. توصلت نتائج الدراسة لوجود أثر لنظام الأجر على الإلتزام التنظيمي للموظفين في مؤسسة محل الدراسة، ولقد انحصر هذا الأثر خصوصا على بعد نسب التعويضات، في حين سجلنا عدم وجود أثر لبعد نسب الاقتطاعات، مما سمح باقتراح توصيات قابلة للتطبيق تساهم في تحسين نظام الأجر وتعزيز مستوى الإلتزام التنظيمي. This study aims to test the dimensions of the wage system represented in both compensation and deductions rates and their impact on the organizational commitment of private corps employees in the Direction of Trade - Jijel, the questionnaire has been used as a tool to collect data for the study variables, it was distributed on a sample consisting of 60 direction of Trade employees. The results of this study revealed that there is an effect of the wage system on the organizational commitment of employees in the institution that being study, and this effect has been limited especially to the compensation ratios dimension, while we recorded the absence of an effect of the dimension of deductions, which allowed to suggest applicable recommendations that contribute to improving the wage system and enhancing the level of organizational commitment.
The wage system and its impact on the organizational commitment of private corps employees in the Trade Direction - Jijel
مقال
Keywords: نظام الأجر ؛ الإلتزام التنظيمي ؛ مديرية التجارة.; wage System; Organizational Commitment; Trade Direction.